Proceedings of the 27th IEEE/ACM International Conference on Automated Software Engineering 2012
DOI: 10.1145/2351676.2351707
|View full text |Cite
|
Sign up to set email alerts
|

Computing repair trees for resolving inconsistencies in design models

Abstract: Resolving inconsistencies in software models is a complex task because the number of repairs grows exponentially. Existing approaches thus emphasize on selected repairs only but doing so diminishes their usefulness. This paper copes with the large number of repairs by focusing on what caused an inconsistency and presenting repairs as a linearly growing repair tree. The cause is computed by examining the runtime evaluation of the inconsistency to understand where and why it failed. The individual changes that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 21 publications
0
79
0
Order By: Relevance
“…In fact, previous work [5] has shown that independent of the model size, there are on average only 12 possible repairs per inconsistency 3 (see Figure 3). Thus, it is inefficient to enumerate through (e.g.)…”
Section: Repair Generation Approachmentioning
confidence: 88%
See 4 more Smart Citations
“…In fact, previous work [5] has shown that independent of the model size, there are on average only 12 possible repairs per inconsistency 3 (see Figure 3). Thus, it is inefficient to enumerate through (e.g.)…”
Section: Repair Generation Approachmentioning
confidence: 88%
“…We propose here a more efficient approach which generates the exact repair(s) for each inconsistency by analyzing the structure of a consistency constraint and its expected and observed validation results (through observing the constraint's validation) to determine exactly which parts of the inconsistency must be repaired. In the following we briefly outline the approach presented in [5] and explain how this approach has been extended to be able to make repair actions concrete (i.e. a concrete value is known).…”
Section: Repair Generation Approachmentioning
confidence: 99%
See 3 more Smart Citations